Prevalence of neurophobia and its related perceptions on neurology among junior doctors in Malaysia / Nor Azam Ismail - Nor Azam, Ismail (2021)
The phenomenon of neurophobia, which is described as the fear of neurological subjects, is not well studied among Malaysian doctors. The aim of the study was to determine the prevalence of neurophobia among Malaysian junior doctors, to determine the perceived level of interest, knowledge, confidence and phobia in Neurology, to assess the association and prediction between different demographic backgrounds of the junior doctors, reasons for Neurology being perceived as a difficult subject, and perceived usefulness of different methods of learning neurology on their perceived difficulty of neurology. The study employed an online, questionnaire-based data collection method distributed among junior doctors through various social media platforms. Descriptive, Chi-square, and binomial logistic regression analyses of the results showed that among 389 junior doctors surveyed, 76.3% had neurophobia. Nine factors; Gender (X2 (1)=20.439, p<0.001), perceived level of interest (X2 (1)=14.044, p <0.001), perceived level of knowledge (X2 (1)=24.659, p <0.001), perceived level of phobia (X2 (1)=11.637, p =0.001), perceived level of confidence (X2 (1)=26.857, p <0.001), neurology's reputation as a difficult subject (X2 (1)=16.553, p <0.001), neurology covers such a large number of diagnoses (X2 (1)=12.971, p <0.001), textbooks (X2 (1)=6.241, p=0.012) were statistically significant factor associated with perceiving neurology as a difficult subject. Eight predictors were identified for perceiving neurology as a difficult subject: Females (OR=0.318, p<0.000, 95% CI 0.173-0.582), twinning undergraduate training (OR=0.316, p=0.009, 95% CI 0.133-0.749), perceiving neurology's reputation as a iv difficult subject as an important reason (OR=0.401, p=0.005, 95% CI 0.211-0.762), perceiving neurology covers a large number of diagnoses as an important reason (OR=0.325, p=0.002, 95% CI 0.162 - 0.653), scoring peer learning as useful (OR=0.281, p=0.012, 95% CI 0.104 - 0.757), perceived good knowledge of neurology (OR=5.897, p=0.01, 95% CI 1.521-22.859), those interested in neurology (OR=2.697, p=0.027, 95% CI 1.118-6.508), and having confidence in managing complicated neurology cases (OR=2.660, p=0.002, 95% CI 1.434-4.933). The results obtained differ from other studies on neurophobia, and more studies are required to understand the phenomenon better.